2017
DOI: 10.3390/ijms18112497
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Mitigates Inflammatory Responses Induced by Vascular Endothelial Growth Factor in Mouse Retinal Photoreceptor Cells through Suppression of Nuclear Factor Kappa B

Abstract: Retinal vascular endothelial growth factor (VEGF) increased by neovascularization is well known as a pathogenic factor in ocular neovascular diseases. However, it is still unclear how retinal neurons are damaged by VEGF. The aims of this study are to demonstrate the inflammatory protein expression regulated by VEGF using mouse photoreceptor-derived cells and the protective effect of quercetin against VEGF-induced inflammatory response. Expression and phosphorylation of protein and expression of mRNA were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Moreover, we found that quercetin could suppress VCAM-1 expression in mouse aorta and cultured HUVECs ( Figure 3 , Figure 4 and Figure 5 ). This finding was consistent with that reported by Lee et al, showing that quercetin suppressed vascular endothelial growth factor-induced inflammatory responses, such as the translocation of nuclear factor kappa B, the upregulation of adhesion molecules and MMPs, and the downregulation of tight junction molecules [ 22 ]. In the present series of experiments, the tendency was shown that VCAM-1 expression in aorta tissue was lower in the quercetin treated sample than control sample.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that quercetin could suppress VCAM-1 expression in mouse aorta and cultured HUVECs ( Figure 3 , Figure 4 and Figure 5 ). This finding was consistent with that reported by Lee et al, showing that quercetin suppressed vascular endothelial growth factor-induced inflammatory responses, such as the translocation of nuclear factor kappa B, the upregulation of adhesion molecules and MMPs, and the downregulation of tight junction molecules [ 22 ]. In the present series of experiments, the tendency was shown that VCAM-1 expression in aorta tissue was lower in the quercetin treated sample than control sample.…”
Section: Discussionsupporting
confidence: 93%
“…Ferulic acid, baicalein, coptisine, and wogonin downregulate NF-κB signaling ( Chen et al, 2017 ; Lampiasi and Montana, 2017 ; Shimizu et al, 2018 ), while berberine, catapol, and quercetin modulate PPAR-γ and NF-κB activities ( Le et al, 2015 ; Chuang et al, 2016 ; Li et al, 2016 ; Park, 2016 ; Wang Y.C. et al, 2016 ; Lee et al, 2017 ; Mahmoud et al, 2017 ). Additionally, pathway and functional enrichment analysis for putative targets revealed that DGLHD mainly regulated TNF-α, NF-κB, PPAR, and PI3K/Akt signaling pathway, which were all involved in fibrogenesis ( Seki and Schwabe, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, baicalein, berberine, ferulic acid, catapol, coptisine and quercetin contained in DGLHD have been reported to exert anti-inflammatory and/or anti-fibrotic effects via inhibition of NF-κB pathway ( Sun et al, 2010 ; Le et al, 2015 ; Xu et al, 2015 ; Wang Y.C. et al, 2016 ; Chen et al, 2017 ; Lampiasi and Montana, 2017 ; Lee et al, 2017 ; Shimizu et al, 2018 ). Thereby, it seems reasonable that DGLHD repressed the development of fibrogenesis by modulating NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress activates host immune and other defense mechanisms that under prolonged insult exacerbate photoreceptor cell death by promoting exaggerated inflammatory responses (Kohno H et al, 2013, Rashid K et al, 2019. Flavonoids can inhibit the inflammatory reactions by suppressing the expression of pro-inflammatory genes and adhesion molecules implicated in the pathogenesis of retinal degeneration (Bian M et al, 2017, Cao X et al, 2010, Lee M et al, 2017. Indeed, bright light-induced retinal inflammation in Abca4 −/− Rdh8 −/− mice was remarkably suppressed by quercetin and myricetin, which at the molecular level correlated with the reduction of the expression of inflammatory markers.…”
Section: Downloaded Frommentioning
confidence: 99%